Strategic Drift and Organizational Culture in Oil and Gas Company of Nigeria - Monica C. Gajere; Danjuma T. Nimfa (International Journal of Engineering and Management Research, 2021)
The main purpose of this study was to examine the impact of strategic drift on organizational culture in the oil and gas company of Nigeria. The study used a survey research design. The primary method of data collection was employed for the study. A quantitative approach and multiple regression analysis were adopted for testing the hypotheses. Findings from the study revealed that strategic resilience, organizational flexibility and managerial culture have significant and positive relationships with organizational culture in the Oil and Gas Company of Nigeria, while has not significantly impacted the organizational culture in the Oil and Gas Company of Nigeria. The paper provides that strategic managers of the oil and gas companies in Nigeria need to build and improve on strategic resilience capability. The managers of oil and gas companies should encourage the widespread use of formal and informal organizational flexibility as a strategy to meet business, individual needs and good culture for sustainability. The research provides some contributions in theory and strategic management. The paper has provided insight for management thinking in terms of strategic drift and organizational culture in the Oil and Gas companies of the developing economy which has not been studied in the previous literature.